Experimental investigation of the high-pressure SCR reactor impact on a marine two-stroke diesel engine. (1st March 2023) - Zhang, Yinguang; Xia, Chong; Liu, Diantao; Zhu, Yuanqing; Feng, Yongming
Highlights: Effect of HP-SCR reactor on pulse effect in the exhaust pipe. NOx reduction rate is 84.7 %, and the maximum fuel consumption penalty of the engine doesn't exceed 1 g/kWh. Effect of HP-SCR reactor on HC, CO, and CO2 emission of low-speed marine engine. Abstract: The high-pressure selective catalytic reduction (HP-SCR) system arranged before the turbine is more suitable for high-power marine low-speed engines to reduce NOx emission. However, the HP-SCR reactor will cause an increase in engine exhaust back pressure, affecting its performance and brake-specific fuel consumption (BSFC). The 10WM marine low-speed two-stroke diesel engine and its HP-SCR system are taken as the research object in this paper. The engine performance and emissions in International Maritime Organization (IMO) Tier II and Tier III modes are tested by bench experiments. The effects of the HP-SCR reactor on engine performance parameters, emission characteristics, and pulse effect in exhaust pipe are obtained. The research showed that when the HP-SCR reactor is used, the BSFC of the engine will slightly increase, but the maximum will not exceed 1 g/kWh. The weighted specific emission of NOx is 2.09 g/kWh, which can meet Tier III emission regulations. In addition, under the Tier II mode, the engine exhaust pipe has a noticeable pulse effect. The exhaust gas temperature before the turbine is about 30 °C higher than that after the cylinder. However, under Tier III mode, the pulse effect in the exhaust pipe disappears completely. In addition to the fact that the HP-SCR reactor weakens the linear velocity of exhaust gas, the main reason is that the urea injection unit reduces exhaust gas temperature by 36 ∼ 47 °C.